2013
DOI: 10.3174/ajnr.a3385
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Prognosis of Patients under Conscious Sedation Requiring Emergent Intubation during Neuroendovascular Procedures

Abstract: BACKGROUND AND PURPOSE: Neuroendovascular procedures are performed with the patient under conscious sedation (local anesthesia) in varying numbers of patients in different institutions, though the risk of unplanned conversion to general anesthesia is poorly characterized. Our aim was to ascertain the rate of failure of conscious sedation in patients undergoing neuroendovascular procedures and compare the in-hospital outcomes of patients who were converted from conscious sedation to general anesthesia with thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 22 publications
(22 reference statements)
1
16
0
1
Order By: Relevance
“…It is worth mentioning that our cohort presented a higher conversion rate from CS to GA compared with previously reported works (13, 23), with nearly 20% (7/36) of GA patients receiving a non-standard anesthetic management with respect to local policy (i.e., CS-policy). Unfortunately, the reasons for these conversions were not recorded, meaning that any deteriorations of the patients who required an emergent intubation cannot be ruled out.…”
Section: Discussionmentioning
confidence: 49%
“…It is worth mentioning that our cohort presented a higher conversion rate from CS to GA compared with previously reported works (13, 23), with nearly 20% (7/36) of GA patients receiving a non-standard anesthetic management with respect to local policy (i.e., CS-policy). Unfortunately, the reasons for these conversions were not recorded, meaning that any deteriorations of the patients who required an emergent intubation cannot be ruled out.…”
Section: Discussionmentioning
confidence: 49%
“…12,16,25 It is interesting to note that despite these witnessed complications requiring emergent conversion from CS to GA, most centres preferred CS for EVT. This is in good agreement with previous studies which reported a 1.7-14% conversion rate from CS to GA during EVT procedures.…”
Section: Discussionmentioning
confidence: 99%
“…This is in good agreement with previous studies which reported a 1.7-14% conversion rate from CS to GA during EVT procedures. 12,16,25 It is interesting to note that despite these witnessed complications requiring emergent conversion from CS to GA, most centres preferred CS for EVT. Conscious sedation often requires less manpower, is possibly less costly and may be associated with earlier initiation of rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…Because patients with more severe strokes were more often intubated and treated under GA, this might directly or indirectly explain their worse outcome, even if severity of illness was mostly corrected for in the studies. The number of studies and patients investigated for CS certainly supports that this may be feasible for EST and that conversion to GA in case of emergency may also be feasible and only rarely (2–14%) necessary . On the basis of the current retrospective data a task force of the Society for Neuroscience in Anesthesiology and Critical Care (SNACC) published a consensus paper on ‘Anesthetic Management of Endovascular Treatment for Acute Ischemic Stroke’.…”
Section: Controversy Of Intubation Vs No Intubation For Estmentioning
confidence: 98%